1997
DOI: 10.1079/bjn19970013
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal responses to dietary diacylglycerol of hepatic enzymes of fatty acid synthesis and oxidation in the rat

Abstract: The activities of hepatic enzymes of fatty acid synthesis and oxidation were compared in rats fed on diacylglycerol and triacylglycerol. In the first trial, rats were fed on diacylglycerol or triacylglycerol (rapeseed oil) for 14 d. The diacylglycerol preparation contained 65-2 g and 32*6 g fatty acids/100 g total fatty acids as 1,3-species and 1,2-species respectively. Fatty acid compositions of these dietary lipids were similar. Dietary acylglycerols were added to experimental diets to provide the same amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…12,13 Animal studies have shown that both b-oxidation and expression of lipid metabolism-related genes in the liver and small intestine are enhanced with chronic DAG oil ingestion compared with TAG oil ingestion. [14][15][16] Several human studies have shown greater fat oxidation and/or lower respiratory quotient with short-term DAG oil consumption (single meal, 17 1 8 and 4 days 18 ) compared with TAG oil consumption. Although, these studies examined the shorter-term effects of DAG oil, the longer-term effects of DAG oil consumption remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Animal studies have shown that both b-oxidation and expression of lipid metabolism-related genes in the liver and small intestine are enhanced with chronic DAG oil ingestion compared with TAG oil ingestion. [14][15][16] Several human studies have shown greater fat oxidation and/or lower respiratory quotient with short-term DAG oil consumption (single meal, 17 1 8 and 4 days 18 ) compared with TAG oil consumption. Although, these studies examined the shorter-term effects of DAG oil, the longer-term effects of DAG oil consumption remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…12,14,24) Since the physiological benefits and the mechanisms of SPI and DAG have been established, 11,28) the physiological impacts of simultaneous intake of foods and food components of similar function are expected Values are means AE SEM for five rats. When there was a significant interaction between dietary oil and protein, the significance of differences among groups was analyzed by Fisher's PLSD test.…”
Section: Discussionmentioning
confidence: 99%
“…13) These physiological effects of DAG depend on different metabolic functioning due to structures differing from TG. 14) Simultaneous intake of components with physiologically similar functions involved in lipid metabolism appears to be more beneficial for reduction of the risks of life-style related diseases. In this study, therefore, we examined the physiological impact of the simultaneous intake of SPI and DAG on lipid profiles and fecal bile acid excretion in rats fed cholesterol-free and cholesterol diets.…”
mentioning
confidence: 99%
“…In relation to the fat acylglycerol composition, Murata et al (1997), Taguchi et al (2001) and Murase et al (2005) also did not find differences in the performance of rats fed DAG or TAG oil-enriched diets. In contrast, Meng et al (2004) reported that the weight gain was lower in rats fed a DAG oil-rich diet, while Kamphuis et al (2003) observed a lesser feeling of hunger and appetite in women fed a DAG oil-enriched diet.…”
mentioning
confidence: 95%
“…In relation to the fat acylglycerol composition, Murase et al (2002) and Meng et al (2004) have reported a reduced accumulation of fat in visceral adipose and subcutaneous tissue, and a reduced fat content in the liver of animals fed 1,3-DAGenriched diets, as compared with those fed TAG of the same FA composition. The presence of dietary 1,3-DAG has been shown to increase β-oxidation of FA in the liver (Murata et al, 1997) and in the small intestine (Murase et al, 2002). We might not have encountered significant differences in fat depots of animals fed re-esterified palm oils because the effect of MAG and DAG might have counteracted the effect of sn-2 SFA.…”
mentioning
confidence: 99%